高齢者の頰部に発症し急速に増大した巨大な異型脂肪腫様腫瘍/高分化型脂肪肉腫の1例 - 深谷, 映吏; 増本, 一真; 松下, 文彦; 内山, 佳之; 加藤, 文度; 渡邉, 賀子 (日本口腔外科学会雑誌, 2021)
Liposarcomas are malignant tumors originating in adipose tissue. They most commonly occur on the lower limbs or retroperitoneum, and extremely rarely in the facial and oral region. Well-differentiated liposarcomas (WDLS) are a subtype of liposarcoma. When they have the same histological and chromosomal characteristics as atypical lipomatous tumor (ALT), they are designated ALT/WDLS. ALT/WDLS comprise mature adipose tissue with atypical nuclei, are locally invasive and of low malignancy. Herein, we present a case report of an 89-year-old woman with ALT/WDLS in the left cheek who was referred to our department having presented with painless swelling in that region. Initial examination revealed a soft rubbery 40 × 30mm mass. On enhanced MRI, the tumor exhibited fat signals and did not take up contrast. The clinical diagnosis was lipoma. The patient refused surgery so was only followed up. However, the tumor grew rapidly, measuring 80 × 50 × 40mm by 13 months after presentation. Enhanced MRI then showed mixed low uptake of contrast. Histopathological examination of a biopsy showed lipoma. Because we strongly suspected liposarcoma, we removed the tumor under general anesthesia, resulting in a histopathological diagnosis of ALT/WDLS. There was no evidence of recurrence during two years and six months of follow-up.